The Weight of Age in the Use of the Imperfect and Pluperfect Subjunctive (-ra/-se) - Samamé Rispa, Anahís (2021)
This paper focuses on analyzing the use of the imperfect and pluperfect subjunctive -ra/-se in the Spanish spoken in Lima from a variational perspective. From a sample of university speakers of three age groups (young, adults and older), it is proposed to determine if -ra is displacing -se, for which it will be analyzed if the election of one or another variant is conditioned by age. It is concluded that the use of -ra exceeds that of -se in the sample studied. Likewise, it is found that while young people prefer more -ra than adults and older people, the later ones use more -se, which confirms that one form is displacing the other in the Spanish of Lima.